2017
DOI: 10.1016/j.joca.2016.12.022
|View full text |Cite
|
Sign up to set email alerts
|

Do foot & ankle assessments assist the explanation of 1 year knee arthroplasty outcomes?

Abstract: 12Objective: Whilst a number of risk factors for poor patient reported outcomes (PROMs) following do not further explain post-operative KA outcomes. Consideration should also be given to address 27 pre-operative foot pain when attempting to achieve a good clinical outcome for KA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…Hallux valgus is associated with both knee and foot pain as well as the presence of nodal OA [11] and an increase in disability levels in women with knee OA [12]. A recent study showed that approximately 13–39% of individuals with knee OA, or at-risk of knee OA, have concurrent foot pain that adversely affects their functional status [13], knee symptoms [14], and clinical outcomes 1 year following total knee arthroplasty (TKA) [15]. …”
Section: Introductionmentioning
confidence: 99%
“…Hallux valgus is associated with both knee and foot pain as well as the presence of nodal OA [11] and an increase in disability levels in women with knee OA [12]. A recent study showed that approximately 13–39% of individuals with knee OA, or at-risk of knee OA, have concurrent foot pain that adversely affects their functional status [13], knee symptoms [14], and clinical outcomes 1 year following total knee arthroplasty (TKA) [15]. …”
Section: Introductionmentioning
confidence: 99%
“…This highlights the importance of including foot pain measures within the clinical assessment of knee and hip symptoms, particularly in those with a diagnosis of OA. Given that it is known that people with pre-operative foot pain are more likely to have poorer clinically important outcomes following knee arthroplasty (13), the potential for foot pain to negatively impact concurrent knee and hip symptoms and vice versa should therefore be considered.…”
Section: Discussionmentioning
confidence: 99%
“…This highlights the importance of including foot pain measures within the clinical assessment of knee and hip symptoms, particularly in those with a diagnosis of OA. Given that it is known that people with pre-operative foot pain are more likely to have poorer clinically important outcomes following knee arthroplasty [18], the potential for foot pain to negatively impact concurrent knee and hip symptoms and vice versa should therefore be considered.…”
Section: Discussionmentioning
confidence: 99%